Living in the mugano – the partitioned ndau in the Mozambique-Zimbabwe borderland - Patrício, Marta (2015)
The Mozambique-Zimbabwe border is one of longest boundaries in Southern Africa. Running for about 1,231 km, it divides eastern Zimbabwe and central Mozambique. At the same time, it is one of the least researched borders in Southern Africa. While some research has been carried out along this border focusing on refugees (Hughes 1999), on labour and migration (Tornimbeni 2005, Newitt & Tornimbeni 2008), on agriculture and environmental conservation (Tornimbeni 2007, Hughes 2009), and on land politics and traditional authorities (Tornimbeni 2010, Florêncio 2005), very little is known about how the borderland communities perceive and relate to the boundary.